Spousal concordance in joint and separate households: Survey evidence from Nepal - Ambler, K; Doss, C; Kieran, C; Passarelli, S (Elsevier, 2021)
In household surveys, husbands and wives who are asked the same set of survey questions often provide different responses. The levels of concordance in responses to questions about who owns assets and makes decisions in a household may hold valuable information about household dynamics and women’s well-being. These relationships may be especially indicative in the South Asian context where couples often reside in joint households with the husbands’ parents, resulting in different power structures. Using data from Nepal, we study patterns of concordance between spouses on survey questions regarding household asset ownership and decision making. We analyze these patterns separately for couples that reside with the husband’s parents and those that do not. We consider concordance regarding both the asset ownership and decision making of wives and individuals other than the respondent couple. We find that discordance regarding wives’ asset ownership and decision making is both substantial and systematic. Wives are much more likely than husbands to report their own participation in asset ownership and decision making, in both joint and separate households. Regarding the involvement of others, the modal response in joint households is concordance that others own assets and make decisions; however, wives are more likely than husbands to acknowledge this. Spousal concordance that wives own assets or make decisions, and discordance in which wives report that they own assets or make decisions, are both correlated with some improved measures of wives’ well-being. In households with in-laws present, concordance that others are involved is correlated with worse outcomes for wives. These results highlight that spousal concordance is not necessarily indicative of wives’ well-being, especially in joint households.